2016
DOI: 10.3389/fpsyg.2016.00804
|View full text |Cite
|
Sign up to set email alerts
|

Infants Prefer Female Body Phenotypes; Infant Girls Prefer They Have an Hourglass Shape

Abstract: Adolescents and adults show preferences for male and female body shapes consistent with evolutionary theories of reproductive fitness and mate selection. However, when these preferences for females with narrow waists (i.e., 0.7 waist-to-hip ratio) and men with broad shoulders (i.e., mesomorphic body shape) emerge during the lifespan is largely unknown. To address this knowledge gap, eye-movements were tracked in 146 infants (3–18 months of age) during computer presentation of three-dimensional human figures va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 58 publications
3
15
1
Order By: Relevance
“…Such sensitivity to WHR early in life is in direct contrast with previous work suggesting that such preferences do not emerge until childhood (Johnson et al, ). However, it should be noted that the WHR was not the only feature of the stimuli that differentiated the high and low mate value images in Alexander et al (). For example, the low mate value images had higher BMIs than the high‐mate value images meaning that in addition to the WHR changing between the images, the shapes of other body parts (e.g., arms and legs) also changed and could have influenced infants' preferences.…”
Section: Waist‐to‐hip Ratio Sensitivity In Early Infancymentioning
confidence: 90%
See 4 more Smart Citations
“…Such sensitivity to WHR early in life is in direct contrast with previous work suggesting that such preferences do not emerge until childhood (Johnson et al, ). However, it should be noted that the WHR was not the only feature of the stimuli that differentiated the high and low mate value images in Alexander et al (). For example, the low mate value images had higher BMIs than the high‐mate value images meaning that in addition to the WHR changing between the images, the shapes of other body parts (e.g., arms and legs) also changed and could have influenced infants' preferences.…”
Section: Waist‐to‐hip Ratio Sensitivity In Early Infancymentioning
confidence: 90%
“…Previous research suggests that sensitivity to WHR develops in childhood between 4 and 5 years of age, implying that such sensitivity is a function of years of socialization and is possibly reliant on conceptual development (Johnson, Lurye, & Tassinary, ). However, a recent study by Alexander, Hawkins, Wilcox, and Hirshkowitz () found that female, but not male, infants show preferences for ‘ideal’ body types. This finding suggests not only that sensitivity to WHR may be acquired much more rapidly than previous reports, but also that such development varies by the sex of the observer.…”
Section: Waist‐to‐hip Ratio Sensitivity In Early Infancymentioning
confidence: 99%
See 3 more Smart Citations